(untitled) (Journal of Information and Communication Technology, 2003)
Due to the changing nature of Internet technology and user needs, continuous web evaluation has become very important in determining the usability of web sites. However, web designers often face problems in identifying the right criteria for evaluation. Despite the growing number of guidelines and other literature on web design and evaluation, each of them varies in terms of quality, coverage, relevancy, and suitability. With this in mind, a study using IGV approach was carried out to identify key generic criteria that need to be taken into consideration by designers or others when assessing the overall usability of web sites. The results of the study include a comprehensive list of the identified usability criteria that were grouped into 7 major factors – screen appearance, content, accessibility, navigation, media use, interactivity, and consistency.